Lysosome-targeting BODIPY-derived Hantzsch ester for nitric oxide detection and imaging in live cells - Tang, Fang; Gao, Chang; Liu, Jin-Yu; Lu, Zhong-Lin; He, Lan; Ding, Ai-Xiang (Sensors and actuators. B, Chemical, 2021)
•A new BODIPY-derived Hantzsch ester has been developed as an off-on fluorescence probe to detect nitric oxide.•The fluorescence amplification is 140 folds, and the limit of detection is 47 nM.•This probe can specifically target lysosomes.•This probe is capable of sensing and imaging the endogenous NO generation and distribution in lysosomes. Nitric oxide (NO) is an epoch-making cellular signaling molecule and has been widely recognized as a fundamental participant in many physiological and pathological processes. The development of robust probes for indicating its existence, concentration, and especially the spatiotemporal messages in the subcellular location of live cells is emerging as one of the most intriguing research subjects. In this work, we report the design and synthesis of a new dihydropyridine-derived boron dipyrromethene (BODIPY) sensor (Lyso-DHP) modified with a morpholine unit for sensitively and selectively detecting NO in 100 % aqueous media and lysosomes of living cells. Time/pH-dependent fluorescence experiments in the presence of NO revealed Lyso-DHP was a fast-response probe in an acidic environment. Lyso-DHP showed an ultrahigh “switch-on” ratio (140-fold fluorescence enhancement) and ultralow detection of limit (LoD, 47 nM). Moreover, Lyso-DHP itself and its NO-induced aromatization product Lyso-PY were both cytocompatible. Live-cell-related localization studies including the exogenous/endogenous NO imaging and lysosome targeting demonstrated good cell permeability and feasibility and dependability for application in live cells. The obtained results indicated that Lyso-DHP was capable of tracing subcellular NO with high specificity, precision, and brightness.